Character Centered Leadership and Its Influence on Employee Loyalty in Sharia Banking: A Case Study in the South Sulawesi Region - Jabani, Muzayyanah; Muhajir, Muhammad Nur Alam; Muang, Muh. Shadri Kahar; Kamal, Fasiha (Technium Social Sciences Journal, 2022)
This study aim to find out how the influence of Character Centered Leadership on Loyalty of Bank Mandiri Syariah employees in South Sulawesi.This study uses quantitative research with the type of hypothesis testing, while the data sources in this study are primary data and secondary data.Based on the results of the study, it was found that there was an influence of Character Centered Leadership on the loyalty of Bank Mandiri Syariah employees in South Sulawesi with the result that the R value = 0.582a this value can be interpreted that the relationship between the two research variables exists but is categorized as weak. Through this it is also obtained that the value of R Square = 0.338 can be interpreted that the variable (X) has a 33.8% contribution effect on the variable (Y). It was also found that based on the significance value test (Sig) was 0.000 > 0.05, the effect of Character Centered Leadership on the loyalty of Bank Mandiri Syariah employees in South Sulawesi was significant.